KARAKTERISTIK BURUH INDUSTRI DAN PREFERENSI TERHADAP PEMILIHAN RUMAH KOST DI KELURAHAN NGEMPON KECAMATAN BERGAS KABUPATEN SEMARANG TAHUN 2016 - Madyaratri, Dwiga Selly; Hardati, Puji; Arifien, Moch. (Geo-Image, 2017)
This research aims to determine the distribution of boarding houses, characteristics of industri workers, factors that affect the preferences of election a boarding house and the preferences of election a boarding house for industry workers. Techniques of data collection using questionnaires, documentation and field measurements. Data were analyzed using spatial analysis and percentage descriptive analysis. The results showed that the distribution of boarding houses tend to be located in industri area which are neighborhood unit 01, unit 04, unit 05, and unit 06. Characteristics of industry workers are divided into three aspects, namely a) demographic aspects including age, sex and marital status; b) socio-cultural aspects covering the status and position of industry workers, the latest education and the origin of industry workers; and c) economic aspects that include income and expenditure of industry workers in a month. Factors that affect the preferences of election a boarding house are internal factors and external factors. Internal factor is the characteristics of industry workers, while the external factors are divided into four factors: physical factors, accessibility factors, environmental factors, and boarding house facilities.The preferences of election a boarding house for industry workers there a four, among them a) ease of access to the work site and the infrastructure that is the main reason industry workers choose where to stay in boarding house; b) a clean, safe and comfortable boarding house environment, which is the second reason; c) cheap boarding house rental fees is the third reason; and d) completeness of public facilities boarding house which is the last reason industry workers in choosing boarding house.